(untitled) (Research, Society and Development, 2022)
The understanding that epistemology should be considered one of the main tools aimed at training teachers with holistic characteristics, from a technical point of view, has been consolidated for a long time, whether in the context of initial or continuing education. The main objective of this article is to draw the attention of the various actors belonging to this field of study on the contribution of Karl Popper and the rationalist current to the epistemological debate, in fact, here begins a series of articles on which, later, other currents of the philosophy of science will be treated. In order to contribute to this aspect, this article seeks to detail some characteristics of the Austrian philosopher’s work beyond the contextualization that places him historically, such as: the demarcation of Science; human knowledge and deduction and; the concept of verisimilitude. The chosen methodological path includes a severe bibliographic review, based on introductory manuals of philosophy of science, as well as classic texts and recent high-impact articles in that area. As a conclusion, it is expected to highlight the need for a coherent and conscious epistemological debate in the context of teacher training with sustainable and explicit proposals in the pedagogical project of training courses.